The effect of COVID-19 on vulnerable populations in the US and UK: an international scoping review - Audrey Funwie; Mehrunisha Suleman; Zackary Berger (Ethic@: an International Journal for Moral Philosophy, 2023)
Context: Comparing the Covid-19 related experiences of vulnerable groups can help to improve public health.?The United States and the United Kingdom are both characterized by underfunded public health in the context of racist systems. We reviewed differences in Covid-19 outcomes between groups in the US and UK and compared intergroup differences between the two countries.